ARTIFICIAL INTELLIGENCE AND OPERATIONAL EFFICIENCY OF TEXTILE ENTERPRISES IN UZBEKISTAN - Yormatov Ilmidin Toshmatovich (Scholars Digest Publishing, 2024)
This article scrutinizes the integration and utilization of artificial intelligence (AI) within Uzbekistan's textile enterprises and its consequential impact on operational efficiency. It deliberates on the advantageous aspects of AI adoption, including process optimization, human resource management, data analytics, and decision-making capabilities. Moreover, it sheds light on the challenges and considerations inherent in AI implementation, offering practical recommendations for the effective deployment of this technology in Uzbekistan's textile industry. This exploration underscores the transformative potential of AI in driving productivity and competitiveness within the textile sector of Uzbekistan.
Keywords: artificial intelligence, textile enterprises, operational efficiency, production processes, personnel management, data analysis, decision making, process optimization, technologies in the textile industry.